(untitled) (Research, Society and Development, 2020)
The objective of this article is to evaluate the use of the teaching model based on active methodology and to encourage students to learn autonomously and participatively, based on real problems and situations. The methodology used was the comparative analysis between teaching laboratory classes with the traditional method in a class of 19 students in 2019, and another class of 19 students in 2020 through the COVID-19 pandemic with the application of active methodologies education. An autonomous search for knowledge was introduced, through scientific research, seeking the development of practical class scripts for the discipline of Risk Control Process Methods in a Health and Safety Engineering course at a university in Minas Gerais, Brazil . Due to the COVID-19 pandemic, education environments have grown considerably, due to the suspension of face-to-face classes at educational institutions across the country. Since then, the search for the use of digital platforms such as Google Meet and other virtual tools has increased significantly. It is concluded that the active methodology used for practical classes contributed considerably to the learning of the students involved, mainly in their motivation. Where an average grade increase of 7.8 points was obtained in the year 2019 before the pandemic using the traditional methodology, to an average of 9.3 in 2020 during the pandemic using the active methodology.